2015
DOI: 10.3347/kjp.2015.53.4.403
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Immunodominant B-cell Epitope Regions of Reticulocyte Binding Proteins in <i>Plasmodium vivax</i> by Protein Microarray Based Immunoscreening

Abstract: Plasmodium falciparum can invade all stages of red blood cells, while Plasmodium vivax can invade only reticulocytes. Although many P. vivax proteins have been discovered, their functions are largely unknown. Among them, P. vivax reticulocyte binding proteins (PvRBP1 and PvRBP2) recognize and bind to reticulocytes. Both proteins possess a C-terminal hydrophobic transmembrane domain, which drives adhesion to reticulocytes. PvRBP1 and PvRBP2 are large (> 326 kDa), which hinders identification of the functional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
4
12
0
Order By: Relevance
“…PvRBP1a-34 and PvRBP1b-32 were observed to have low antigenicity with the vivax patient serum samples. Our results also confirmed the results from our previous study and another report 39 40 41 . PvRBP1b had relatively low antigenicity among the PvRBP family proteins compared with the high antigenicity of PvRBP2c 40 41 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…PvRBP1a-34 and PvRBP1b-32 were observed to have low antigenicity with the vivax patient serum samples. Our results also confirmed the results from our previous study and another report 39 40 41 . PvRBP1b had relatively low antigenicity among the PvRBP family proteins compared with the high antigenicity of PvRBP2c 40 41 .…”
Section: Discussionsupporting
confidence: 93%
“…Our results also confirmed the results from our previous study and another report 39 40 41 . PvRBP1b had relatively low antigenicity among the PvRBP family proteins compared with the high antigenicity of PvRBP2c 40 41 . The PvDBP-RII domain contains polymorphic sequences that may affect antibody recognition for protection against parasite invasion 42 43 .…”
Section: Discussionsupporting
confidence: 93%
“…Because these antibody levels are associated with age, they likely reflect cumulative exposure to the parasite, similar to previous findings on different fragments of PvRBP1a from Brazil ( 27 ). Consistent with our findings, a recent study exploring potential immunodominant B-cell epitopes revealed that the N-terminal fragment of PvRBP2c is highly immunogenic, while that of PvRBP1b is the least immunogenic among PvRBP antigens tested ( 28 ).…”
Section: Discussionsupporting
confidence: 91%
“…It is therefore likely that PvDBP would need to be combined with further antigens targeting alternative invasion ligands. Members of the PvRBP family are recognized by antibodies from vivax-positive patients [ 11 , 16 ], and populations living in endemic areas [ 17 , 18 ]. Yet, an in-depth characterization of the immune responses to these proteins, as well as the role of antibodies to PvRBPs in the acquisition of immunity to malaria is lacking.…”
Section: Introductionmentioning
confidence: 99%